Effect of number of medications and use of potentially inappropriate medications on frailty among early-stage older outpatients - Yuya Uragami; Kazuhiro Takikawa; Hajime Kareki; Koji Kimura; Kazuyuki Yamamoto; Naomi Iihara (BMC, 2021)
Abstract Background Frailty is an urgent concern among an aging population worldwide. However, the relationship between frailty and number and types of medications has not been studied in detail among early-stage older patients, and it is unclear what prescriptions may have a role in preventing frailty. This study aimed to clarify the effects of number of medications and use of potentially inappropriate medications (PIMs) on frailty among early-stage older outpatients in Japan. Methods A cross-sectional study was undertaken. Frailty scores and medications of outpatients aged 65-74 years who regularly visited community pharmacies were investigated. Frailty scores were classified as 0 (non-frailty), 1-2 (pre-frailty), and ≥ 3 (frailty). The association between frailty and number of medications was analyzed by age and compared between PIM use and non-use groups. The proportion of patients who used PIMs was also analyzed by frailty score. Results Of 923 older outpatients, 49 (5.3%) and 318 (34.5%) patients had frailty and pre-frailty scores, respectively. The numbers of medications among patients with pre-frailty and frailty were significantly higher than among those with non-frailty (p <  0.001 for both). A similar increase was shown for PIM use groups aged 69-71 and 72-74 years, but not for the PIM use group aged 65-68 years and all groups without PIM use. An increasing linear trend was observed for the relationship between the proportion of patients who used any PIM, as well as some subcategories of PIMs (such as NSAIDs, benzodiazepines, loop diuretics and antithrombotic drugs) and frailty score. Conclusions Unnecessary medication use among early-stage older outpatients, especially patients aged ≥69 years who use PIMs and many medications, seems to be associated with frailty, but further research is needed to confirm these findings.